Choriocapillaris in Age-Related Macular Degeneration - Giovanni Neri; Chiara Olivieri; Sonia Serafino; Pasquale Viggiano; Paola Marolo; Michele Reibaldi; Enrico Borrelli (Türk Oftalmoloji Dergisi, 2024)
Age-related macular degeneration (AMD) is a multifactorial disease characterized by progressive alterations of different retinal structures ultimately leading to vision loss. Among these, the choriocapillaris (CC) has been found to be affected in different stages of AMD. In this review we provide a discussion on the different stages of AMD, focusing particularly on the alterations involving the CC. This has been possible thanks to the introduction of optical coherence tomography-angiography, a recently developed imaging technique which allows the detection of blood flow in choroidal vessels. Therefore, the aim of this review is to provide a description of the various alterations involving the CC in the different stages of AMD.